Regenerative Innovation and Ethical Design Based on Eco-Humanism And Their Impact on Corporate Performance And Market Positioning - Naibaho, Togar; Harahap, Muhammad Iqbal; Muda, Iskandar (CV. Civiliza Publishing, 2025)
This study aims to analyze the impact of regenerative innovation and ethical design based on the eco-humanism philosophy on company performance and market position of Rubberwood Baby Safety Harness products. Using sales simulation data for the 2020–2024 period, the study found that the use of regenerative rubberwood materials and the implementation of ethical design contributed significantly to improving the commercial performance of PT X. Product sales increased from 1,250 units (2020) to 2,840 units (2024) with a compound annual growth rate (CAGR) of 21.7%. The initial shipment to Japan in 2021 proved to be a catalyst for increasing international demand, indicated by an increase in export sales from 320 units (2021) to 1,180 units (2024). The results of a simulated consumer survey showed that 78% of respondents considered the use of regenerative materials as a factor in increasing the product's sustainability value, while 72% considered ethical design to increase trust and safety. Internally, the product's contribution to the company's revenue increased from 8.5% to 21.4% during the study period, with a net profit margin increase from 12.3% to 19.8%. These findings indicate that regenerative innovation and ethical design not only enhance the product's ecological value but also strengthen its market position, as evidenced by a distributor perception score of 4.4 out of 5 and a second-place ranking in the eco-friendly baby product category in the Japanese market based on a demand index simulation.